Tindak Tutur Ilokusi dalam Novel Perahu Kertas Karya Dewi Lestari dan Implikasinya terhadap Pembelajaran Bahasa Indonesia - Tara Ashiilah; Putri Ardini; Pretty Grace Banjarnahor Novia Sari Tari; Jernita Simatupang Muhammad Rajali; Juli Ramayani Tesa Arizky Simanjuntak; Anggia Puteri (Journal on Education, 2024)
Language has an important role as a communication tool to convey feelings and attitudes in various situations, including in literary works such as novels. This research aims to identify and describe the types of expressive illocutionary speech acts in the novel Perahu Kertas by Dewi Lestari and analyze their implications for Indonesian language learning, especially in the aspect of pragmatics. The method used in this research is descriptive qualitative with data collection techniques through document study and speech notes. The results show that there are seven types of expressive illocutionary speech acts in this novel, namely praise, thanks, apology, congratulations, expression of admiration, expression of disappointment or anger, and statement of affection. The implementation of the results of this study is expected to be used as an effective teaching material in Indonesian language learning, especially in improving students’ ability to understand pragmatic aspects and daily communication.